Cannadine, G.M Trevelyan - A Life In History - de C. Rosenfeld, Michael (Teaching History: A Journal of Methods, 1994)
David Cannadine’s G. M. Trevelyan: A Life in History is magisterial. As an essay in English historiography it is superb; as a study of English life and letters in the twentieth century it is masterly; and as a model for writing a scholarly life it is without peer. Written with elegance and wit, and an unmistakable patrician air worthy of its subject, Cannadine’s biography has rescued Trevelyan and his work from the limbo of yesterday’s scholarship. Neither nostalgic nor pietistic, Cannadine has made the life of this monumental British historian a key to understanding the development of historical writing in England between 1880 and 1960 as well as the profound transformation that took place in English life during those years.